Sikap Mahasiswa Prodi Pendidikan Bahasa Arab terhadap Penerapan Pembelajaran secara Online di Masa Pandemi Covid-19 - Habibisaid, Nur; Husna, Husna; Maghfur, Alim (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2020)
This study aims to determine the attitudes of Arabic language education study program students towards the application of online learning during the Covid 19 pandemic. The study used a qualitative approach. Data were collected using interview techniques (structured and semi-structured), and documentation. There are three questions to be addressed: Agree and disagree, the obstacles faced and the enthusiasm of students towards the application of online learning. Of the 85 students who were asked through structured interviews using a questionnaire, it was found that as many as 60% of students expressed their agreement with the application of online learning. The obstacles faced when learning online are limited internet quota and signal or network constraints. The enthusiasm of students in participating in online learning is caused by fear of the spread of the corona virus. If the online learning process is continued in the future, students hope that it will only be a supporter and more agree with face-to-face learning as the main thing.